Strategi Pemasaran Digital di Era Dominasi Media Sosial: Transformasi, Tantangan, dan Peluang - Jehalut, Ferdinandus; Subroto, Mohammad Abdullah Risqillah; Hasanuddin, Fadli Awwal (Jurnal Industri Kreatif dan Inovatif, 2025)
This study aims to analyze the transformation, challenges, and opportunities of digital marketing strategies in the era of social media domination. Based on the phenomenon of increasing connectivity and digital participation among Indonesians, with internet penetration reaching 80.66%, this study highlights how changes in consumer behavior and technological advances are shifting the marketing paradigm from product-centric to human-centric. The method used is a qualitative-conceptual approach based on literature studies with content analysis of various recent scientific literature in the fields of digital marketing, consumer behavior, and information technology. The results show that digital marketing strategies now require the integration of artificial intelligence and human empathy through the five pillars of Marketing 5.0: data-driven, predictive, contextual, augmented, and agile marketing. The main challenges include information fatigue, data trust crisis, and digital literacy gap, while the greatest opportunities lie in the integration of online-offline strategies, storytelling based on human values, and consumer collaboration in brand value creation. This research concludes that the success of digital marketing does not only depend on technology, but on a company's ability to humanize technology. Inclusive digital literacy and public data ethics are needed to ensure that digital transformation runs smoothly.